STEM Integrated Flipped Classroom Learning Tools on Biodiversity Materials to Improve Students' Critical Thinking Skills (FMIPA UNNES, 2022)
Thinking skills of students in Indonesia are still in the low category. This is evidenced by the results of Indonesia's PISA score which is still far from the international score. The COVID-19 pandemic has forced learning to be done online at home. So in this case it is necessary to update the learning model that is applied. This study aims to produce learning tools that can be used to improve students' critical thinking skills during the COVID-19 pandemic. The method used is Research and Development which consists of 10 stages of research. This research was conducted in the odd semester of the 2021/2022 academic year in class X MIPA 1 SMA N 1 Pagelaran. The sampling technique used is probability with the type of simple random sampling. Data collection was done by using questionnaires, tests, and interviews. The learning device developed using the flipped classroom model which is integrated with STEM to improve students' critical thinking skills during the COVID-19 pandemic. The results showed that the learning tools developed, including the syllabus, lesson plans, worksheets, and evaluation tools were suitable for use in learning. The syllabus gets a feasibility percentage of 93.75% and the lesson plans get a feasibility percentage of 86.45% from learning experts. The LKS developed got a feasibility percentage of 82.50% from material experts and 93.33% from media experts. While the evaluation tool gets a percentage of 94.33% from evaluation experts. The results of the small-scale trial showed a very good response from the teacher to the experimental device developed, with an average percentage of 95.31% for the syllabus, lesson plans of 94.79% and LKS of 95.00%. The LKS developed got a very good response from students with a percentage of 90.10% and produced 30 items that were worthy as an evaluation tool. The results of the trial using the evaluation tool using the paired sample test obtained a value of Sig (2-tailed) = 0.00 < (0.05) which means that there is a significant influence on the application of STEM-integrated flipped classroom learning tools with students' critical thinking skills. Based on the results of the study, it can be concluded that the development of STEM-integrated flipped classroom learning tools to improve students' critical thinking skills is feasible to use in learning.